Generation of a grid of monthly rainfall for Africa (1900-2000) - (:unkn) unknown (My University, 2010)
The Montpellier Laboratory of HydroSciences, HSM, has developed a database of monthly rainfall for Africa using archives of tropical African rainfall data. This data was compiled in large part by ORSTOM and attests to their extensive experience in management of hydro-climatic data. The data grids created make it possible to distribute gridded rainfall data at half square degrees, which is useful for research in Africa while respecting the confidentiality of the raw data which remains the property of national services. The raw data is subject to a series of in-depth critical analyses or each gauging station in order to correct or eliminate false or questionableinformation. This work has three objectives: i) submit an online inventory of existing rainfall stations for all countries; ii) generate a series of homogeneous rainfall data called “reference series”; iii) construct half-square degree monthly rainfall grids for the African continent over the period 1900-2000, available for free on the SIEREM site http://www.hydrosciences.fr/sierem.
Keywords: African Research